Cover Image. Issue 2 (1st January 2020) - Tavor, Ido; Botvinik‐Nezer, Rotem; Bernstein‐Eliav, Michal; Tsarfaty, Galia; Assaf, Yaniv
Abstract : COVER ILLUSTRATION Evidence for short‐term, motor learning‐related structural plasticity in the adult human brain was revealed using diffusion MRI. Structural changes were detectable in cortical and sub‐cortical brain regions of non‐musicians after only 45 minutes of pianotraining. This work highlights the dynamic nature of of the adult human brain; and the use of diffusion MRI as a rapid and sensitive biomarker for gray‐matter learning‐driven plasticity.